Cash, Care, Access And Dignity: Welfare Conversion In Indonesia’s PKH Plus Elderly Assistance - Liawati Suntiana (DAS Institute, 2026)
This article examines how PKH Plus, a provincial social assistance programme for older persons in East Java, contributes to elderly well-being beyond the direct transfer of money. Using a field-monitoring-based descriptive design, the study analyses structured monitoring data from 231 elderly beneficiaries observed during the 2025 implementation cycle and integrates relevant literature on old-age poverty, social pensions, informal care, health access, dignity and behavioural transformation. The findings show strong delivery integrity: all monitored respondents received the full IDR 500,000 quarterly benefit, no respondent reported deductions, and all perceived the assistance as useful for daily expenditure. However, delivery success coexists with fragile welfare conversion. Approximately 42.4% of respondents were physically unhealthy, 26.8% could not perform daily activities independently, 65.8% could not meet daily needs without assistance, 43.7% needed help during withdrawal, and KIS utilisation remained incomplete despite high PBI-JKN ownership. The article proposes a cash-care-access-dignity framework. Cash reduces immediate expenditure pressure; care enables practical use of assistance; access connects beneficiaries to disbursement, health and learning services; and dignity protects older persons as rights-bearing subjects. PKH Plus is therefore most transformative when cash delivery is integrated with family resilience, accessible services and behaviour-sensitive programme governance. The findings support sustainable, human-centred welfare policy aligned with SDG 1, SDG 3, SDG 10 and SDG 16.